REDUPLIKASI BAHASA JEPANG DALAM NOVEL IKITEMASU, 15 SAI KARYA MIYUKI INOUE - Budiarti, Sarli (Humanis; Volume 2. No. 3. Maret 2013, 2013)
The title of this study is “ReduplikasiBahasaJepangdalam Novel Ikitemasu, 15 SaiKarya Miyuki Inoue”. The data source of this study was taken from Japanese novel entitled Ikitemasu, 15 Sai.The study used agih methods and informal methods. The theory were used to analyze the main character of the novel was taken from the theory of form reduplication by Koizumi (1995) and the theory of mean reduplication by Simatupang (1983). There are two forms analysis of reduplication form: stem reduplication (gokan no juufuku) and stem and affixes reduplication (gokanjuufuku to setsuji). Semantically, Japenese reduplication in the novel Ikitemasu, 15 Sai by Miyuki Inoue showed five meanings, namely meaning of diversity, distributive, intensive, plural or singular, and the meaning of reduplication which states doing something repeatedly or continuosly. Keyword: Reduplication, Form, Mean
Keywords: Reduplication, Form, Mean